Two Yeast La Motif-containing Proteins Are RNA-binding Proteins that Associate with Polyribosomes - Sobel, Suzanne G. (The American Society for Cell Biology, 1999)
We have characterized two Saccharomyces cerevisiae proteins, Sro9p and Slf1p, which contain a highly conserved motif found in all known La proteins. Originally described as an autoantigen in patients with rheumatic disease, the La protein binds to newly synthesized RNA polymerase III transcripts. In yeast, the La protein homologue Lhp1p is required for the normal pathway of tRNA maturation and also stabilizes newly synthesized U6 RNA. We show that deletions in both SRO9 and SLF1 are not synthetically lethal with a deletion in LHP1, indicating that the three proteins do not function in a single essential process. Indirect immunofluorescence microscopy reveals that although Lhp1p is primarily localized to the nucleus, Sro9p is cytoplasmic. We demonstrate that Sro9p and Slf1p are RNA-binding proteins that associate preferentially with translating ribosomes. Consistent with a role in translation, strains lacking either Sro9p or Slf1p are less sensitive than wild-type strains to certain protein synthesis inhibitors. Thus, Sro9p and Slf1p define a new and possibly evolutionarily conserved class of La motif-containing proteins that may function in the cytoplasm to modulate mRNA translation.